Implementasi Penginputan Data Perjalanan Dinas Menggunakan Paket Program Niaga dengan Teknik Lookup - Icha Miranti Irzan; Silalahi, Dinah Makhroza (Ali Institute or Research and Publication, 2024)
AbstractThe input of official travel data at the Medan City Regional People's Representative Council (DPRD) is done using a commercial software package and lookup technique. Official travel is an integral part of government agency activities. The commercial software package was chosen as a solution to simplify the official travel data input process. This research includes needs analysis, system design, implementation, and evaluation of results. The lookup technique is applied to expedite data search and retrieval, enhance processing speed, and reduce potential input errors. The research methodology involves interviews with end-users, observation of the data input process, and collection of implementation results.The research findings indicate that the implementation of the commercial software package with the lookup technique significantly improves the efficiency of official travel data input. Users reported a reduction in the time required to fill out official travel forms, as well as an improvement in the accuracy of inputted data. Additionally, the system allows for more structured and easily traceable data management. The conclusion of this journal is that the utilization of the commercial software package with the lookup technique can be an effective solution in enhancing the efficiency and accuracy of official travel data input in government agency settings. It is hoped that the results of this research can serve as a reference for other organizations or institutions seeking to improve efficiency in official travel data management through the use of information technology. Keywords: Implementation, official travel, business software package, lookup technique